Successful passive sentence comprehension among Danish adolescents with autism spectrum disorders. (March 2018) - Jensen de López, Kristine; Schroeder, Kristen; Gavarró, Anna
Background and aims: Language abilities vary greatly across children with autism spectrum disorders (ASD). In the present study, we investigate passive sentence comprehension, which has been underexplored among individuals with autism spectrum disorders and found to be delayed among other clinical populations. This study is the first to assess grammatical comprehension among Danish-speaking adolescents with autism spectrum disorders. Methods: Fifteen Danish-speaking adolescents with autism (mean age: 14.9 years; age range: 13–18 years) participated in a picture selection task assessing comprehension of passive sentences relative to active sentences. We compared our findings for adolescents with autism spectrum disorders to those of 15 typically developing Danish-speaking adolescents matched for age and nonverbal reasoning as measured by the Matrix subtest of the WISC-IV/WAIS-IV. We also analyzed associations between passive comprehension and nonverbal reasoning. Results: The results showed ceiling effects for both groups on all sentence types indicating that Danish adolescents with autism spectrum disorders do not face problems comprehending passive sentences. However, when considering variation within the autism spectrum disorder group, correct passive comprehension was highly significantly associated with nonverbal reasoning for the autism spectrum disorder group ( r = .75), while this was not the case for the typically developing adolescents. Analyses of the few errors produced showed a preference for Theta-role reversal errors in the autism spectrum disorder and the typically developing groups. Conclusions: Danish-speaking adolescents with high-functioning autism spectrum disorders do not show impairment in passive sentence comprehension. Correlation analyses however show that for adolescents with autism spectrum disorders, passive sentence comprehension is associated with nonverbal reasoning. We discuss how these results can be viewed as consistent with the few previous studies on passive comprehension in individuals with autism spectrum disorders. Implications: Our study provides additional cross-linguistic evidence that passive comprehension is not problematic for individuals with high-functioning autism spectrum disorders. The finding of the relationship between nonverbal reasoning and passive sentence comprehension may inform clinical best practices as children with autism spectrum disorders who underperform in measures of nonverbal reasoning may benefit from additional receptive language screening.